Differences and correlations between horizontal and vertical single-leg jump performance, dynamic balance, and ankle dorsiflexion range of motion in male amateur rugby players according to playing positions - Tondelli, Eduardo (2024)
Fil: Tondelli, Eduardo. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas; Argentina